2009
DOI: 10.1111/j.1834-7819.2008.01086.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of changing the chewing region on mandibular movement

Abstract: Background: In the shortened dental arch condition, little is known of how patients adapt their jaw function during mastication to the new oral environment. This study aimed to investigate the changes in mandibular movements when the chewing region was changed from the first molar to the first premolar. Methods: Thirty clinical residents with natural dentitions were recruited. The subjects were asked to chew a piece of beef jerky using either the first molar or the first premolar on the preferred chewing side.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…The restoration of masticatory function is an important aim in dentistry when patients present with extensive tooth loss. Some studies have shown that patients may compensate for posterior tooth loss by chewing longer (2), by swallowing larger food particles or by selecting a softer diet (3).…”
Section: Introductionmentioning
confidence: 99%
“…The restoration of masticatory function is an important aim in dentistry when patients present with extensive tooth loss. Some studies have shown that patients may compensate for posterior tooth loss by chewing longer (2), by swallowing larger food particles or by selecting a softer diet (3).…”
Section: Introductionmentioning
confidence: 99%
“…The current finding adds significant evidence that the molar region as the main occluding area may be of primary importance in maintaining the masticatory ability in good condition, regardless of the main occluding area being on either natural teeth or artificial teeth. Hashii et al 9 investigated the changes in mandibular movements when the chewing region was changed from the first molar to the first premolar. The result demonstrated that when the chewing region was changed from the first molar to the first premolar, the chewing cycle referred to as chopping type was predominant, as observed during the chewing of soft food.…”
Section: 13mentioning
confidence: 99%
“…[5][6][7][8] On the other hand, in the partially or fully edentulous condition with reduced occlusal support, the occluding area is considerably limited and the food platform area changes accordingly to enable mastication using the remaining natural teeth as well as the artificial teeth. Hashii et al 9 stated that when the chewing region was changed from the first molar to the first premolar, the patient would be forced to chew with minimal lateral deviation of the mandible in spite of the toughness of the food. Therefore, it is important to know the location of the main occluding area in such patients when providing instructions on how to use their jaws during mastication with reduced occlusal support.…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that for subjects with RPDs, the main occluding areas were located more anteriorly than those in the group treated with implant prostheses . Others reported that loss of posterior occlusal support was related to condylar displacement and that the food platform area changed accordingly to enable mastication using the remaining natural teeth, so when the chewing region was changed from the first molar to the first premolar, the mandible would be forced to deviate to chew . The abovementioned studies suggested that reduction or loss of posterior occlusal support caused traumatic overloads on the anterior teeth.…”
Section: Discussionmentioning
confidence: 99%